A Water‐Stable Ionic MOF for the Selective Capture of Toxic Oxoanions of SeVI and AsV and Crystallographic Insight into the Ion‐Exchange Mechanism. (17th March 2020) - Sharma, Shivani; Desai, Aamod V.; Joarder, Biplab; Ghosh, Sujit K.
Abstract: Selectively capturing toxic oxoanions of selenium and arsenic is highly desired for the remediation of hazardous waste. Ionic metal–organic frameworks (iMOFs) especially cationic MOFs (iMOF‐C) as ion‐exchange materials, featuring aqueous phase stability, present a robust pathway for sequestration of the oxoanions owing to their ability to prevent leaching because of their ionic nature. On account of scarcity of water‐stable cationic MOFs, the capture of oxoanions of selenium and arsenic has been a major challenge and has not been investigated using iMOFs. Herein, we demonstrate large scale synthesis of cationic MOF, viz. iMOF‐1C that exhibits selective capture of oxoanions of Se VI (SeO4 2− ) and As V (HAsO4 2− ) in water with a maximum sorption capacity of 100 and 85 mg g −1, respectively. This represents among the highest uptake capacities observed for selenate oxoanion in MOFs. Further, the ion‐exchange mechanism was directly unveiled by single crystal analysis, which revealed variable modes of host–guest binding. Abstract : Aufwischen mit MOFs : Die effiziente Entfernung der toxischen Oxoanionen von 79 Se VI und As V ist ein wichtiger Schritt bei der Aufbereitung gefährlichen Abfalls. iMOF‐1C wird als schnelles, hochkapazitives und selektives Sorbens für die Absorption toxischer Se VI ‐ und As V ‐Oxoanionen verwendet. Kristallographische Beweise für den Ionenaustauschprozess werden vorgelegt.